Neutrophils promote the development of reparative macrophages mediated by ROS to orchestrate liver repair - Yang, Wenting; Tao, Yuandong; Wu, Yan; Zhao, Xinyuan; Ye, Weijie; Zhao, Dianyuan; Fu, Ling; Tian, Caiping; Yang, Jing; He, Fuchu; Tang, Li (Nature communications, 2019)
Phagocytes, including neutrophils and macrophages, have been suggested to function in a cooperative way in the initial phase of inflammatory responses, but their interaction and integration in the resolution of inflammation and tissue repair remain unclear. Here we show that neutrophils have crucial functions in liver repair by promoting the phenotypic conversion of pro-inflammatory Ly6C hi CX 3 CR1 lo monocytes/macrophages to pro-resolving Ly6C lo CX 3 CR1 hi macrophages. Intriguingly, reactive oxygen species (ROS), expressed predominantly by neutrophils, are important mediators that trigger this phenotypic conversion to promote liver repair. Moreover, this conversion is prevented by the depletion of neutrophils via anti-Ly6G antibody, genetic deficiency of granulocyte colony-stimulating factor, or genetic deficiency of NADPH oxidase 2 (Nox2). By contrast, adoptive transfer of WT rather than Nox2 −/− neutrophils rescues the impaired phenotypic conversion of macrophages in neutrophil-depleted mice. Our findings thus identify an intricate cooperation between neutrophils and macrophages that orchestrate resolution of inflammation and tissue repair. Neutrophils and macrophages are both involved in the initiation of inflammation, but whether and how they may participate in inflammation resolution is unclear. Here the authors show that neutrophils may mediate the conversion of macrophage into a pro-resolution phenotype via reactive oxygen species production to promote liver repair.